Larangan Ekspor Bijih Nikel menurut Peraturan Menteri ESDM nomor 11 Tahun 2019 dan ketentuan GATT 1994 - Yolanda Al Vionesya; Deli Waryenti; Ari Wirya Dinata (UNIB Press, 2024)
The ban on nickel ore exports carried out by Indonesia through the Minister of Energy and Mineral Resources Number 11 of 2019 made Indonesia sued at the WTO by the European Union for violating the provisions of the 1994 GATT. This article aims to find out how the validity of the nickel ore export ban based on the Minister of Energy and Mineral Resources Number 11 of 2019 and GATT Provisions 1994. To answer the formulation of the problem, this study uses the literature study method. Legal materials obtained both primary legal materials and secondary legal materials are grouped and arranged systematically. Furthermore, the legal material is analyzed qualitatively to make it easier to draw conclusions. The conclusion that can be drawn in this study is that the ban on nickel ore exports is legal according to the Minister of Energy and Mineral Resources Number 11 of 2019, but is contrary to the provisions of GATT 1994. Keywords: Nickel Ore Export Ban; GATT 1994; WTO.